A comparative study of plain and reinforced concrete isolated footings: structural behavior, constructability, and embodied carbon - Arnold, Byron (My University, 2025)
A major challenge confronting architecture, engineering, and construction (AEC) industry is the threat of climate change – an issue to which the industry itself is a significant contributor. As a result, AEC professionals carry a responsibility to improve material efficiency and reduce embodied carbon across common structural systems. One opportunity lies in re-evaluating isolated spread footings, a ubiquitous foundation element in low-rise buildings throughout the United States of America. These footings, typically composed of concrete and reinforcing steel, transfer gravity loads through concrete compression and soil bearing while also resisting incidental shear and moment demands. Although concrete alone can resist axial, shear, and flexural forces to a limited degree, standard practice relies on reinforcing steel to provide adequate shear and flexural capacity. This report examines the ACI 318-19(22) code provisions on plain concrete, reviews design requirements for reinforced foundations, and compares the capacities of plain versus reinforced spread footings subjected to concentrated axial loads of 50, 100, 200, and 300 kip concentric axial loads. Key site and material parameters such as allowable soil bearing capacity (2,000 psf, 3,000 psf, and 4,000 psf) and concrete compressive strength (3,000 psi and 4,000 psi) are varied to enable direct comparisons. To evaluate environmental implications, the increased concrete volume required for plain concrete design is assessed relative to the reduced use of reinforcing steel. It was found that when the ultimate axial load is 50 kips or smaller, plain concrete footings have a reduced environmental impact conversely when the ultimate axial load is 100 kips and greater, reinforced concrete footings have a greater material efficiency that yield a lower embodied carbon. Finally, the report discusses broader constructability and sustainability considerations, including procurement, transportation, and installation impacts associated with each footing type.
Keywords: Embodied carbon; Reinforced concrete; Isolated footing; Plain concrete